Integration of immunization and health care services on the nutritional status of children 6-59 months of age in flood-affected areas of South Punjab - Tanveer, Muhammad (PT. Mega Science Indonesia, 2024)
Child malnutrition remains a serious public health problem in many parts of the developing world, particularly in South and Southeast Asia and sub-Saharan Africa. The situation is exacerbated by natural disasters, particularly floods, which increase the risk of infectious diseases and worsen the nutrition crisis in vulnerable areas. In Pakistan, the 2018 National Nutrition Survey showed high levels of stunting, underweight and wasting among children under the age of five. This study aimed to determine whether integration of immunization and health services can improve the nutritional status of children aged 6-59 months in flood-affected areas of South Punjab, Pakistan. This study used a mixed methods approach, combining a cross-sectional observational study with structured interviews. A sample of 384 children aged 6-59 months was selected through convenience sampling in flood-affected areas. Data were collected through surveys and interviews with families, focusing on maternal feeding practices and factors affecting child nutritional status. Statistical analysis was conducted using IBM SPSS version 25, including frequency distributions for categorical variables and Pearson correlations to determine the association between upper arm circumference (MUAC) and nutritional status, weight, and height. Results showed significant correlations between MUAC and child nutritional status (p=0.035), MUAC and child weight (p=<0.001), and MUAC and child height (p=<0.001). Of the total 384 participants, 60.68% had MUAC more than 12.5 cm, while 39.32% had MUAC less than 12.5 cm. This study confirms the importance of integrating health and immunization services in addressing child malnutrition in disaster-prone areas. Findings show that factors such as parents' socioeconomic status, occupation, education and living environment are significantly related to children's nutritional status.